Etiology of Frenastenia - Ciampi, L. (1922)
Investigations resulting expose, dating from 1913. It was our intention at that time, a contribution to the study of the causes that predispose and determine the mental abnormalities of children, Eugenia Congress to be held in 1914 in Bari (Italy).